IMPLIKASI PENGGUNAAN BASIS DATA DALAM ERA BIG DATA - Aulia Zaky Ibna; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the use of databases in the big data era, with a focus on the challenges and opportunities that arise. The method used is a qualitative descriptive approach, which allows data collection through document analysis. The research results show that large-scale use of databases offers significant opportunities in improving data-based decision making, service personalization, and innovation. However, there are challenges to overcome, including data integration, data quality, security and privacy, and the need for specialized expertise. With the right strategy, organizations can optimize the benefits of big data.